EFFECT OF PHOSPHORUS LEVELS ON YIELD AND QUALITY OF FODDER COWPEA VARIETIES UNDER RAINFED CONDITIONS - S, TIRUMALA REDDY (The Journal of Research ANGRAU, 2026)
The experiment was conducted during kharif, 2018-19 on red loam soils of Regional Agricultural Research Station, Tirupati. The experiment was laid in the randomized block design with factorial concept and each treatment replicated thrice. The results showed that the higher green fodder yield (21,054 kg ha-1) and dry fodder yield (3,473 kg ha-1) was obtained with MFC 08-14 variety. Significantly higher crude protein content (12.15%) was registered with APFC 10 1 variety, while the difference in crude fibre content among the varieties were found non-significant. Among the different levels of phosphorus, application of 60 kg P2 O5 /ha recorded significantly higher green fodder yield (21,590 kg/ha). Crude fibre content was not significantly influenced either by varieties or different levels of phosphorus application under rainfed conditions of Southern Zone of Andhra Pradesh.